Pengaruh Gaya Kepemimpinan Dan Komitmen Organisasi Terhadap Kinerja Karyawan PT. Bumi Rambang Kramajaya Ogan Ilir Sumatera Selatan - Oktarika, Oktarika; Tobari; Agusria, Lesi (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to determine the extent of the influence of leadership style and organizational commitment on employee performance at PT. Bumi Rambang Kramajaya Ogan Ilir, South Sumatra. This research is classified as associative research. The research method used is a qualitative method that is quantified. The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS for Windows Version 26. The data collection technique used in this study is a questionnaire, with a sample size of 88 respondents from a total population of 112 permanent employees. The sampling technique used in this study is Simple Random Sampling. The F-test results show that leadership style and organizational commitment simultaneously have a positive and significant influence on employee performance at PT. Bumi Rambang Kramajaya Ogan Ilir, South Sumatra. The t-test results show that: (1) leadership style has a positive and significant partial influence on employee performance at PT. Bumi Rambang Kramajaya Ogan Ilir, South Sumatra, and (2) organizational commitment has a positive and significant partial influence on employee performance at PT. Bumi Rambang Kramajaya Ogan Ilir, South Sumatra.